Research on the Effects of Poly(Styrene-co-Butyl Acrylate) Emulsions on the Mechanical and Fracture Characteristics of Mortar - Guolin Miao; Peng Jiang; Wenxun Guan; Wanying Ma; Guanzhi Cheng; Xiangtao Li; Yangyang Gao (Applied Sciences)
A series of poly(styrene-co-butyl acrylate) (PSA) emulsions with different monomer ratios were synthesized and characterized, and corresponding polymer-modified mortars were prepared. The effects of polymers with different rigidities on the properties of modified mortars, including the hydration heat, mechanical strength, compressive–flexural ratio, fracture energy, and fracture toughness, were investigated. The results indicate that, as the content of hard monomers in the polymer increases, the fracture energy of the modified mortar first increases and then decreases, consistent with the changes in the polymer’s damping properties. The maximum fracture energy of 211.2 N/m was achieved at a St/BA mass ratio of 4:6 and a polymer-to-cement ratio (P/C) of 15%, which was 2.4 times higher than that of the control mortar group. The fracture toughness of the modified mortar decreased with an increasing polymer doping and decreasing hard monomer content. The compressive–flexural ratio of the modified mortar decreased only with increasing the polymer emulsion dosage, showing no significant correlation with the polymer’s molecular structure.